2002
DOI: 10.1128/iai.70.7.3389-3395.2002
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Type 8 Capsular Polysaccharide AugmentsStaphylococcus aureusVirulence

Abstract: Type 8 capsular polysaccharide (CP8) is the most prevalent capsule type in clinical isolates of Staphylococcus aureus. However, its role in virulence has not been clearly defined. CP8 strains such as strain Becker produce a small amount of capsule on their surface in vitro. In contrast, CP1 strains such as strain M produce a large amount of capsule, which has been shown to be an important antiphagocytic virulence factor. The cap8 and cap1 operons, required for the synthesis of CP8 and CP1, respectively, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 27 publications
4
44
0
1
Order By: Relevance
“…Studies documenting the role of CP8 in virulence were lacking until recently, when Luong and Lee (26) showed that a CP8-overproducing mutant was more resistant to in vitro opsonophagocytic killing by human neutrophils than the parental strain Becker. Likewise, the CP8-overproducing strain persisted longer in the bloodstream, liver, and spleen of infected mice than strain Becker.…”
mentioning
confidence: 99%
“…Studies documenting the role of CP8 in virulence were lacking until recently, when Luong and Lee (26) showed that a CP8-overproducing mutant was more resistant to in vitro opsonophagocytic killing by human neutrophils than the parental strain Becker. Likewise, the CP8-overproducing strain persisted longer in the bloodstream, liver, and spleen of infected mice than strain Becker.…”
mentioning
confidence: 99%
“…Although 11 serologically distinct CPs were identified in S. aureus, the majority of clinical isolates produce CPs of serotype 5 (CP-5) or serotype 8 (CP-8). CPs protect S. aureus against opsonophagocytic killing by polymorphonuclear leukocytes (16,17,25,53,56) and enhance virulence in a number of animal models of staphylococcal infection (34,40,53,54,57). Expression of CPs is known to be influenced by various environmental signals in vitro and in vivo (reviewed in references 35 and 56), and transcription of the cap operon was shown to be modulated by regulatory elements, such as arlRS, agr, ccpA, mgr, sae, and sarA (7,8,23,24,26,27,39,48,52,55).…”
mentioning
confidence: 99%
“…PVL lyses neutrophils at higher concentrations but is a potent stimulator of the release of proinflammatory cytokines such as IL-8 at lower concentrations (Otto, 2010). Some strains of S. aureus are also encapsulated, rendering them resistant to phagocytosis and more virulent in animal models of sepsis (Luong and Lee, 2002;Thakker et al, 1998). Most clinical isolates of S. aureus produce either Type 5 or Type 8 capsular polysaccharide (Roghmann et al, 2005).…”
Section: Pathogenesismentioning
confidence: 99%